Self-concept, self-efficacy beliefs and performance on operations involving fractions among diverse academic groups - dela Rosa, Elmer D. (Philippine journal of psychology, 2010)
"Self-concept and self-efficacy are two mechanisms of personal agency that influence adaptive outcomes such as academic performance."